A longitudinal observational study of user’s perspective of use of Copper-T-380-A inserted in immediate post partum period at a tertiary health care centre in Central India - Trivedi, Anshuli; Kumar Kasar, Pradeep; Tiwari, Rajesh; Shrama, Arvind (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The study aims to understand user’s perspective & complaints due to Copper-T-380A inserted during the immediate postpartum period and to assess the expulsion rate, voluntary removal & mean duration of use. The study also aims to find out reasons for voluntary removal of the IUD. Methods: A longitudinal observational was conducted in tertiary health care center in central India during July-2009 to June 2010. A total of 360 women were enrolled who had immediate post partum IUD insertion. They were interviewed within 48 hours of IUD insertion using a preformed pre tested questionnaire & followed after 1.5, 3 & 6 months in field visits. Results: Of all 74.51% users continued using it upto 22.04±2.66 weeks. The cumulative expulsion rate at the end of 6 months was 16.62%. Most common interval of expulsion was after 3.6±1.5 weeks of IUD insertion. Almost 24.58% users had voluntary removal of IUD after a mean duration of 9.34±3.54 weeks following insertion. The most common reason for voluntary removal of IUD is lower abdominal pain in 13.5%. No instance of uterine perforation, sepsis or hyperpyrexia was noted. Conclusion: Immediate postpartum IUD insertion is safe means of contraception. There is a gradual decline in the discomfort caused by an IUD with time. But there is high expulsion rate.